Methodological Approximation to Evaluate Professor’s Effectiveness: Study of Teachers of the Chair XE0156 University of Costa Rica - Muñoz-Alvarado, José Alfonso (2016)
The following article presents a first approach to more precisely measure the effectiveness of a teacher when giving a course in lectures, specifically in this case Introduction to Economics for non-economists. To achieve this, a probit model was used based on the dynamic model of effectiveness and talent developed by Holmström (1999), in addition to several control variables. It was possible to order the 18 professors of the chair for the second half of 2015 and also to obtain interesting results of the control variables, such as the optimal size that each group should have.